THE INFLUENCE OF FAMILY EDUCATION ON EARLY ADOLESCENT PERSONALITY IN SUHUD HAMLET, RINTIS VILLAGE, SILANGKITANG DISTRICT, SOUTH LABUHANBATU REGENCY - Morukama Mikiko; Rosdiana; Istiana (Universitas Negeri Medan, 2025)
This This research aims to find out whether parents are not maximizing family education so that it has an impact on teenagers' personalities. This research aims to determine the influence of family education on the personality of early adolescents in Suhud Hamlet, Rintis Village, Silangkitang District, South Labuhanbatu Regency. The method used in this research was quantitative descriptive with a sample of 41 early adolescents in Suhud Hamlet, Rintis Village, Silangkitang District, South Labuhanbatu Regency. The instrument used in the data collection technique was a questionnaire and the data analysis technique used was simple linear regression and t test. Based on data processing with simple linear regression, the linear regression equation is Ŷ = 39.62 + 0.604X. The results of hypothesis testing with the t test obtained a value > namely 2.879 > 1.697. This means that there is an influence of family education on the personality of early adolescents in Suhud Hamlet, Rintis Village, Silangkitang District, South Labuhanbatu Regency. So it can be concluded that the better the family education that parents apply to their children, the better the personality of the early teenager will be. Family education has an influence on creating a good and quality generation, because the role of the family has a big influence on the formation of a child's personality.